Vein graft thrombi, a niche for smooth muscle cell colonization – a hypothesis to explain the asymmetry of intimal hyperplasia. (30th March 2016) - Blaas, I.; Heinz, K.; Würtinger, P.; Türkcan, A.; Tepeköylü, C.; Grimm, M.; Doppler, C.; Danzl, K.; Messner, B.; Bernhard, D.
Abstract : Essentials Vein graft failure is the most frequent late onset complication of coronary artery bypass grafting. Cuff technique‐based interposition mouse model including new anticoagulation regime was conducted. Early vein graft thrombi may serve as a niche for smooth muscle cell colonization. The focal character of early thrombi may form the basis for the asymmetry of intimal hyperplasia. Summary: Background: Autologous saphenous veins are widely used in coronary artery bypass grafting; however, 10 years after surgery, 40% of grafts are completely occluded, and another 30% show reduced blood flow. Objective: In the past, the central processes and signaling pathways responsible for this loss of patency have been identified. However, one central finding in the process of graft failure is so far not understood: the asymmetric character of intimal hyperplasia. It was the goal of the present study to address this aspect. Methods: By the use of a cuff technique‐based vein interposition mouse model with a new anticoagulation regime, alterations in vein grafts were analyzed 1 h, 1 day, 2 days, 3 days, 7 days and 21 days after reperfusion by means of immunolabeling, histochemistry, and high‐resolution ultrasound. Results: The novel and major finding of this study is that the vein graft thrombus may serve as a niche that is infiltrated and colonized by smooth muscle cells (SMCs). Fibroblast growth factor‐1 and platelet‐derived growth factor‐B may be the SMC‐attracting factors in the thrombus. The focal character of early thrombi may define the focal and asymmetric character of vein graft intimal hyperplasia. Conclusions: Inhibiting the formation and reducing the size of early thrombi is an old concept for reducing vein graft failure. However, in light of the present new findings obtained under a clinic‐like anticoagulation regime, early vein graft thrombus prevention/size reduction should be revisited in the prevention of graft failure.